2011
DOI: 10.1159/000332848
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Pemphigus in Korea: Retrospective Analysis of 199 Patients

Abstract: Background: Pemphigus is the most common and severe autoimmune bullous disease in Korea. Objective: The aim of this clinical study was to evaluate the clinical features, treatment modalities and long-term prognosis of pemphigus in Korea. Methods: We conducted a retrospective analysis of 199 patients diagnosed with pemphigus vulgaris (PV) and pemphigus foliaceus (PF) between 1993 and 2008. Complete and partial remissions were evaluated according to the definitions proposed by the International Pemphigus Committ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
2
17
0
2
Order By: Relevance
“…It should be noted that we did not include the PV patients treated with rituximab (which may be a susceptibility factor for infection). Kim et al found that there was no difference in prednisolone alone or prednisolone plus adjuvant with regard to prognosis and time to remission in PV patients [19]. …”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that we did not include the PV patients treated with rituximab (which may be a susceptibility factor for infection). Kim et al found that there was no difference in prednisolone alone or prednisolone plus adjuvant with regard to prognosis and time to remission in PV patients [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the study suggests rituximab to be an effective and safe drug for patients who are resistant to conventional therapy. [43]…”
Section: Autoimmune Vesiculobullous Disordersmentioning
confidence: 99%
“…Combination with other immunosuppressants, such as azathioprine, methotrexate, mycophenolate mofetil, cyclophosphamide and cyclosporine, allows for a steroid-sparing effect. Other treatment options include intravenous immunoglobulin, plasmapheresis, photopheresis, extracorporeal immunoabsorption, gold salts and dapsone [4,5,6]. Nevertheless, many patients never obtain remission, and others remain poorly controlled.…”
Section: Introductionmentioning
confidence: 99%